A study on consumers brand preference towards purchasing car in tirunelveli district - Dhinakaran, Samson Joe (Journal of Management and Science, 2012)
The consumer attaches considerable importance to the brand image in the purchase of products.Several branded cars are sold in Tirunelveli. There is cut turn out competition among manufacturing companies.Therefore every company has to make a study about the psychology of consumers and their attitude towards brand preference of cars. There fore studying psychology of consumers and to recommend to the companies about the consumers brand preference towards cars was taken by the researcher. Hence there is strong competition among sellers. The necessity arrives among these forms to conduct a study about consumer brand preference. The researcher realizing their necessity and understanding the present problem, undertaking this study and wants to give suggestion for this problem in his findings at the last.